(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses psychological and pedagogical approaches to the formation of resistance to stress among military university cadets. The relevance of the topic is due to the high requirements for the professional training of future specialists operating under conditions of increased psycho-emotional stress. The theoretical foundations of the concepts of “stress tolerance”, “psychological stability”, “adaptation” are analyzed, psychological and pedagogical factors influencing the development of resistance to stress are identified. Special attention is paid to the targeted impact in the learning process: the introduction of elements of psychotraining, the development of self-regulation skills, the formation of positive motivation and reflective thinking. Methods and practical recommendations for increasing the stress tolerance of cadets are presented, including the use of group forms of work, modeling of stressful situations and support from a teacher and a psychologist. The importance of an integrated and systematic approach to the formation of stress tolerance as an important component of cadets’ professional readiness is emphasized.